Asleep at the wheel? Responsible innovation in quantum computing - Inglesant, P; Ten Holter, C; Jirotka, M; Williams, R (Routledge, 2021)
Quantum computing is an emerging set of technologies which promise to transform aspects of computing in ways that, though increasingly defined, are still largely theoretical. Responsible Innovation (RI) asserts that technologies with potentially transformative capacity on society should be approached with care and forethought; this paper is based on applying RI in one of the UK’s National Quantum Technology Hubs.